COMPARATIVE EVALUATION OF DETOXIFICATION STRATEGIES FOR SUGARCANE BAGASSE HYDROLYSATE - Z. Mushtaq; N. Asghar; M. Waheed (Journal of Animal and Plant Sciences, 2019)
Lignocellulosic agricultural biomass generated by agriculture sector remains underutilized which can be a key source for bio-development. Biomass from dilute acid hydrolysate comprise a considerable quantity of fermentable sugars while carbonyl degradation of compounds (Furans, acetic acid, and phenolic compounds) exhibit severe toxicity to fermentation microbes. The study was carried out to hydrolyse the sugarcane bagasse and to optimize different detoxification strategies. Sugarcane bagasse was hydrolysed with acid at 121°C for 20, 40 and 60 minutes. Afterwards analysis of detoxification methodologies like over-liming (pH 6; pH 9.0), vacuum evaporation (3-fold; 5-fold) and charcoal treatment (1%, 30 min; 5%, 60 minutes) were carried out. The results indicate that concentrations of sugars and degradation products was observed to enhance with an increase of hydrolysis time. Overliming utilizing calcium hydroxide resulted in 50% decline of furfurals while substantial decrease of phenolic compounds was observed. Five-fold vacuum evaporated concentration of hydrolysate exhibit considerable decrease in the concentration of acetic acid and furans. Furfural and hydroxymethyle furfural were removed completely removal with 5% treatment of charcoal at 60°C while acetic acid and phenolics also reduced. The detoxified hydrolysate can be applied in industry for production of several important products.
Keywords: Agricultural biomass; Comparative evaluation; Detoxification; Fermentation inhibitors; Sugarcane bagasse